MONITORING DAN PERINGATAN DINI TERHADAP PENYAKIT MENULAR PADA PUSKESMAS DAN BALAI PENGOBATAN DI KOTA KUPANG - H. F.J Lami; S.I. Pella (Jurnal Media Elektro, 2012)
Currently, the surveillance officers reported infectious disease monitoring data conventionally. Data from surveillance officers recapitulated every month to report on DINKES KOTA KUPANG. The impact is processing data are experiencing delays to be processed and reported to DINKES NTT. SIMOK-W2, based on SMS gateway and Web, designed to overcome the problem of delay in the reporting of data W2. By the implementation of this system, the reporting mechanism is done by sending an SMS to the server DINKES and then will be processed and published on the website SIMOK-W2.